Incel Activity on Social Media Linked to Local Mating Ecology - Brooks, Robert C.; Russo-Batterham, Daniel; Blake, Khandis R. (Psychological Science, 2022)
Young men with few prospects of attracting a mate have historically threatened the internal peace and stability of societies. In some contemporary societies, such involuntary celibate—or incel—men promote much online misogyny and perpetrate real-world violence. We tested the prediction that online incel activity arises via local real-world mating-market forces that affect relationship formation. From a database of 4 billion Twitter posts (2012–2018), we geolocated 321 million tweets to 582 commuting zones in the continental United States, of which 3,649 tweets used words peculiar to incels and 3,745 were about incels. We show that such tweets arise disproportionately within places where mating competition among men is likely to be high because of male-biased sex ratios, few single women, high income inequality, and small gender gaps in income. Our results suggest a role for social media in monitoring and mitigating factors that lead young men toward antisocial behavior in real-world societies.